Study on the Utilization of National Health Insurance Participants for Contribution Assistance Recipients Jambi City - Dwi Noerjoedianto; Adila Solida; Arnild Augina Mekarisce (Lembaga Pengembangan Kinerja Dosen, 2022)
The coverage of JKN PBI participation is higher than that of non-PBI participants, but the utilization of health services by JKN PBI participants in Indonesia is still relatively low. This study aims to determine what factors are related to the utilization of health services for PBI group National Health Insurance (JKN) participants in Jambi City. This study is a quantitative study using a cross sectional approach. The sample amounted to 106 samples with a sampling technique using accidental sampling. The independent variables in this study were education, occupation, knowledge, attitudes, perceptions of health conditions, affordability and information, while the dependent variable was the utilization of health services. Data were obtained by filling out questionnaires by respondents. Data analysis was performed using univariate and bivariate (chi-square) tests. The results of this study indicate that most of the 61.3% of respondents do not use health services. Based on statistical tests in this study indicate that factors related to the utilization of health services are knowledge (0.000), attitudes (0.003), perception of health conditions (0.012), and information (0.000). And there is no relationship between education (0.147), occupation (0.295) and affordability (0.787) with the utilization of health services for participants of the National Health Insurance (JKN) PBI group. There is a relationship between the variables of knowledge, attitudes, perceptions of health conditions and information with the utilization of health services for the participants of the National Health Insurance for the PBI Group in Jambi City.